Traumatic brain injury in the intensive care unit : association between the Glasgow coma score and the intensive care unit mortality; the Botswana experience - Mkubwa, Jack Joseph (Stellenbosch : Stellenbosch University, 2021)
ENGLISH SUMMARY : Background: Traumatic brain injury prevalence in Botswana is high and this, coupled with a small population, may reduce productivity. There is no previous study on the association between mortality in traumatic brain injury and the Glasgow coma score in Botswana although global literature supports its existence. Objectives Our primary aim was to determine the association between the initial Glasgow Coma scale score and the time to mortality of adults admitted with TBI at the Princess Marina Hospital, Botswana, between 2014 and 2019. Secondary aims were to assess the risk factors associated with time to mortality and to estimate the mortality rate from TBI. Methods This was a retrospective cohort design, medical record census conducted from 1st January 2014 to 31st December 2019. Results: In total, 137 participants fulfilled the inclusion criteria and majority, 114 (83.2%) were male with mean age 34.5 years. The initial GCS score and time to mortality were associated (aHR: 0.69; 95% CI: 0.508-0.947). Other factors associated with time to mortality included constricted pupil (aHR: 0.12; 95% CI: 0.044-0.344), temperature (aHR: 0.82; 95% CI: 0.727-0.929), and subdural haematoma (aHR: 3.41; 95% CI: 1.819-6.517). Most cases of TBI, 74 (54%) were due to road crashes. Mortality was 48, 35% (95% CI: 27.1% to 43.6%) and entirely from severe TBI. Conclusion: The study confirmed significant association between Glasgow coma score and mortality. Males were mainly involved in TBI. These findings lacked external validity due to a small sample size and therefore a larger multi-centre study is required for validation.